2008
DOI: 10.1007/s00192-008-0720-x
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study utilizing a patient educational brochure at a vesicovaginal fistula hospital in Nigeria, Africa

Abstract: Introduction and Hypothesis A pilot study exploring the utility and feasibility of use of a vesicovaginal fistula (VVF) patient educational brochure. Methods Women awaiting or recently having undergone VVF surgery examined a 6-paneled educational brochure detailing the causes, treatment options and prevention methods of VVF. Participants answered demographic questions and gave detailed responses to a questionnaire that addressed the brochure material. Results Convenience sample of fifty patients with a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Treatment of depression in this population may therefore benefit from cognitive behavioural approaches (van’t Hof, Cuijpers, Waheed, & Stein, 2011), which could help to replace such thoughts with alternative medical explanations of the fistula. Although counseling interventions for this population exist (Gerten, Venkatesh, Norman, Shu’aibu, & Richter, 2009; Johnson et al, 2010), none utilise cognitive behavioural approaches within a religious framework. A religious framework that directly addresses religious and spiritual struggles that are experienced as a result of a stigmatised medical condition may be more salient in this setting than a purely secular framework (Tarakeshwar, Pearce, & Sikkema, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of depression in this population may therefore benefit from cognitive behavioural approaches (van’t Hof, Cuijpers, Waheed, & Stein, 2011), which could help to replace such thoughts with alternative medical explanations of the fistula. Although counseling interventions for this population exist (Gerten, Venkatesh, Norman, Shu’aibu, & Richter, 2009; Johnson et al, 2010), none utilise cognitive behavioural approaches within a religious framework. A religious framework that directly addresses religious and spiritual struggles that are experienced as a result of a stigmatised medical condition may be more salient in this setting than a purely secular framework (Tarakeshwar, Pearce, & Sikkema, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Many reports [2][3][4] have investigated prevention, with a particular emphasis on the influence of the local environment and customs, and on the role of the head of the household and/or his mother. As Wegner et al [3] say, "most men would not knowingly ignore signs of obstructed labor…[but they might be unable] to judge when emergency action must be taken."…”
Section: Introductionmentioning
confidence: 99%
“…Given the widespread illiteracy in women with obstetric fistula in limited-resource settings, various teams have used simple tools such as brochures and posters along with simple written materials and verbal instruction [2,5] to help improve understanding the problem and ultimately to help women to take charge of their own recovery.…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of a given population in the learning of anatomy, prevention and treatment of certain health conditions other than pelvic floor, has been documented. Gerten et al conducted a study of an educational brochure in African women with vesicovaginal fistula and observed that this material had the ability to educate women on the causes, treatment and prevention of these fistulas . In this study they also encouraged women to propagate the information learned among their community.…”
Section: Discussionmentioning
confidence: 98%